2022
DOI: 10.3389/fmicb.2022.1022403
|View full text |Cite
|
Sign up to set email alerts
|

Christensenella regulated by Huang-Qi-Ling-Hua-San is a key factor by which to improve type 2 diabetes

Abstract: There is a lot of evidence that oral hypoglycemic drugs work by affecting gut microbes, but the key strains responsible for this effect are not well known. Huang-Qi-Ling-Hua-San (HQLHS), composed of Astragalus Membranaceus, Ganoderma lucidum, Inonotus obliquus, and Momordica charantia L., is a specially designed Chinese medicine formula to treat type 2 diabetes (T2D). In this study, a mouse model of T2D induced by high-fat diet and streptozotocin was used to explore the mechanism of HQLHS in improving hypergly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…showed that the Tenericutes was reduced in diabetic nephropathy after Lycoperoside H treatment, which provided an important reference for the involvement of Tenericutes in the regulation of kidney diseases through “gut-kidney” axis ( Zhang et al., 2022a ). In addition, as a probiotic, Christensenella has been used for the treatment of diabetes, which could enhance the intestinal barrier and reduce intestinal inflammation ( Pan et al., 2022 ). Therefore, hesperidin was found to improve Zn-induced intestinal barrier dysfunction by changing the abundance of Tenericutes and Christensenella, thus alleviating zinc-induced kidney injury via “gut-kidney” axis.…”
Section: Discussionmentioning
confidence: 99%
“…showed that the Tenericutes was reduced in diabetic nephropathy after Lycoperoside H treatment, which provided an important reference for the involvement of Tenericutes in the regulation of kidney diseases through “gut-kidney” axis ( Zhang et al., 2022a ). In addition, as a probiotic, Christensenella has been used for the treatment of diabetes, which could enhance the intestinal barrier and reduce intestinal inflammation ( Pan et al., 2022 ). Therefore, hesperidin was found to improve Zn-induced intestinal barrier dysfunction by changing the abundance of Tenericutes and Christensenella, thus alleviating zinc-induced kidney injury via “gut-kidney” axis.…”
Section: Discussionmentioning
confidence: 99%
“…21 The detection of the main components followed our previous study. 22 Briefly, data acquisition was accomplished in the multiple reaction monitoring (MRM) mode on UPLC-QTRAP-MS/MS based on the highly sensitive SCIEX QTRAP 6500+ mass spectrometry platform.…”
Section: Asle Preparation Methodsmentioning
confidence: 99%
“…Finally, both Christensenella strains altered the composition of the gut microbiome by increasing the abundance of many beneficial microorganisms, such as Bifidobacterium and Phascolarctobacterium . Overall, C. minuta and C. timonesis improved metabolic processes in T2DM mice and mitigated inflammatory responses ( Pan et al, 2022 ).…”
Section: Current Evidence Of the Probiotic Activity Of Chri...mentioning
confidence: 99%